Notes on the genus Epsilon de Saussure, 1855 (Hymenoptera: Vespidae: Eumeninae) with description of a new species - Selis, Marco (Zootaxa, 2017)
The genus Epsilon de Saussure, 1855, is newly recorded from the Moluccas. New distributional records on Epsilon grandipunctatum Gusenleitner, 1996 are provided. Epsilon rufipes Selis, sp. nov. (Moluccas, Aru islands) is described and figured.